Circulating trace elements status in COVID-19 disease: A meta-analysis - Li, Yunhui; Luo, Weihe; Liang, Bin (Frontiers in Nutrition, 2022)
Trace elements are a group of essential metals or metalloids, which are necessary for life, and present in minute amounts. Despite substantial researches highlighting the importance of trace elements in COVID-19 diseases, a thorough evaluation of the levels of circulating trace elements is lacking. Therefore, we conducted a systematic review and meta-analysis to evaluate the trace element status (Zn, Fe, Cu, Mg, and Se) in COVID-19 disease. We also assessed the relationship between circulating trace elements and COVID-19 disease severity and survival status during follow-up. We searched comprehensively MEDLINE, Web of Science, CNKI, and WangFang databases without language restriction, between 1st November 2019 and 1st April 2022. The search identified 1566 preliminary references. A total of 49 studies met the eligibility criteria and were included in the review, and 42 studies were included in the final meta-analysis. Meta-analysis showed that COVID-19 patients had significantly lower circulating Zn (SMD: -0.83, 95% CI: -1.19 to -0.46, P<0.001), Fe (SMD: -1.56, 95% CI: -2.90 to -0.21, P=0.023), and Se (SMD: -0.75, 95% CI: -0.94 to -0.56, P<0.001) levels than healthy controls, and circulating Zn (SMD: -0.47, 95% CI: -0.75 to -0.18, P=0.002), Fe (SMD: -0.45, 95% CI: -0.79 to -0.12, P=0.008), and Se (SMD: -0.27, 95% CI: -0.49 to -0.04, P=0.020) levels were associated with the presence of severity status in COVID-19 patients. Moreover, circulating Fe levels in non-survivors were significantly lower than survivors in COVID-19 (SMD: -0.28, 95% CI: -0.44 to -0.12, P=0.001). However, there was no significant difference in Cu and Mg levels between COVID-19 patients and controls, severity and non-severity status, and survivors and non-survivors (all P>0.05). Taken together, COVID-19 patients displayed lower circulating levels of Zn, Fe, and Se, and their levels were associated with severity status. Moreover, circulating Fe levels may provide part of the explanation for the unfavorable survival status. Therefore, we presumed optimistically that supplements of trace elements might provide an adjutant treatment in the early stages of COVID-19.